Amusing moments in the wild : animals and their friends - Maze, Stephanie (Potomac, Md. : Moonstone Press, 2001)
Photographs and simple text present a variety of animals in amusing poses in their natural habitat
Keywords: Social behavior in animals -- Juvenile literature; Animals -- Habits and behavior